Climate Change, Global Uncertainty, and Operational Costs: Evidence from Indonesian SMEs - Hasani, Syaiful; Murwani, Danardana; Sopiah, Sopiah; Winarno, Agung; Fatmah, Dinda (Asian Journal of Applied Economics, 2026)
Background and Objectives: Small and Medium Enterprises (SMEs) play a crucial role in economic development and employment generation, particularly in emerging economies. In Indonesia, SMEs represent more than 99% of business entities, contribute approximately 61% of national GDP, and employ about 97% of the workforce. Despite their economic importance, SMEs are increasingly exposed to environmental and macroeconomic pressures that threaten operational sustainability. Climate change disrupts production through extreme weather events, energy price volatility, and instability in raw material supply chains. At the same time, global economic uncertainty reflected in inflationary pressures, exchange-rate volatility, and geopolitical tensions creates additional operational risks that may increase firms’ cost structures. These challenges are particularly relevant for SMEs in the garment and clothing sector, which is characterized by labor intensive production and strong supply chain dependence. Although previous studies have examined environmental uncertainty and firm performance, limited research has explored the mechanisms through which climate change and global uncertainty influence SMEs’ operational costs. In particular, digital technology adoption and digital financial literacy may function as adaptive capabilities that help SMEs respond to environmental turbulence, although such investments may also generate short-term adjustment costs. In addition, the role of financial inclusion in shaping these cost dynamics remains underexplored. Therefore, this study examines how climate change and global economic uncertainty influence SMEs’ operational costs through the mediating roles of digital technology adoption and digital financial literacy, as well as the moderating role of financial inclusion. Methodology: This study employs a quantitative research design using cross-sectional survey data collected from 270 owners and managers of SMEs operating in Indonesia’s garment and clothing sector. Respondents were selected through purposive sampling to ensure their involvement in business operations, digital technology adoption, and financial decision-making. Data were collected using a structured questionnaire with Likert-scale indicators adapted from established studies. The main constructs include climate change exposure, global uncertainty, digital technology adoption, digital financial literacy, financial inclusion, and operational costs. The analysis also includes control variables, namely firm size, firm age, sub-sector, regional characteristics, and input utilization. The empirical analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM), which is suitable for examining complex mediation and moderation relationships. Key Findings: The empirical results reveal several important findings. First, climate change has a positive and significant effect on SMEs’ operational costs, indicating that environmental disruptions increase production, energy, and logistics expenses. Second, both climate change and global economic uncertainty significantly stimulate the development of adaptive capabilities, particularly through increased digital technology adoption and improved digital financial literacy. Third, digital technology adoption and digital financial literacy significantly increase operational costs in the short term. This finding reflects adjustment costs associated with digital transformation, including investments in digital infrastructure, employee training, and system integration. Fourth, digital capabilities play a significant mediating role, suggesting that environmental and macroeconomic pressures influence operational costs indirectly through capability development. Finally, the moderating effect of financial inclusion is not statistically significant, indicating that access to financial services alone does not substantially alter how digital capability investments affect SMEs’ operational cost outcomes. Policy Implications: The findings offer several policy implications. First, policymakers should strengthen SME resilience by improving logistics infrastructure, promoting energy-efficient production technologies, and stabilizing supply chain systems to reduce climate-related cost pressures. Second, governments should expand SME digital transformation initiatives, including training programs in e-commerce management, digital accounting systems, and digital supply chain platforms. Third, because digital capability development requires substantial initial investment, financial policy support is needed to reduce SMEs’ transitional cost burdens. Policy instruments such as tax incentives for digital technology adoption, subsidized digital infrastructure, and low-interest financing programs can facilitate SME digitalization. Strengthening digital capabilities and digital financial literacy can ultimately enhance SME resilience and support sustainable economic development under climate-related risks and global economic uncertainty.